Robotic-assisted thoracoscopic surgery for esophageal duplication cyst in a child: a rare case report and literature insight - Shu, Boshen; Zhang, Shufeng; Gao, Jian; Wang, Lin; Wang, Xiaohui (Frontiers in Pediatrics, 2025)
IntroductionEsophageal duplication cyst (EDC) is a rare congenital anomaly originating from the embryonic foregut. While often asymptomatic, it can present with respiratory symptoms due to compression. We report a rare pediatric case successfully managed using robotic-assisted thoracoscopic surgery (RATS), highlighting the technique's utility in addressing this uncommon foregut malformation.Presentation of caseAn 8-year-old male child, born at term, presented with one week of intermittent left-sided chest pain, bloating, and nausea. Chest radiography demonstrated a high-density mediastinal shadow. Subsequent chest positron emission tomography/computed tomography (PET/CT) and ultrasound (US) revealed a left posterior mediastinal paraspinal cystic mass, necessitating surgical resection. The lesion was diagnosed as an esophageal duplication cyst based on the post-operative pathological report.DiscussionEDC is a rare congenital condition that can become life-threatening due to compression of vital mediastinal structures, particularly the large airways. Non-invasive imaging modalities, including chest radiography, CT, and US, are essential for diagnosis. Surgical intervention is universally indicated to preempt serious complications. RATS has recently emerged as a promising approach, leveraging its technical advantages for this complex procedure.ConclusionTo the best of our knowledge, the present case represents a unique and extremely rare report of EDC management via the Da Vinci robotic surgical system for a pediatric patient in China. The successful application demonstrates the safety and feasibility of RATS for pediatric EDC, expanding the evidence base for this minimally invasive approach.